2023
DOI: 10.3390/ani13071130
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Effects on Physiological and Blood Parameters, and Behavior in Early Fattening Stage of Beef Steers

Abstract: This study was conducted to investigate the effect of heat stress (HS) on physiological, blood, and behavioral parameters, according to the temperature–humidity index (THI), in beef steers. Twelve Korean native beef steers (342.7 ± 13.81 days old, body weight (BW) of 333.0 ± 18.53 kg) were used in this experiment. Beef steers were randomly distributed into three homogenized groups (four beef steers each) for 14 days, namely, threshold (THI = 64–71), mild–moderate (THI = 72–79), and severe (THI = 80–87). Feed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The BUN of Moderate (13.71) and Severe (14.39) showed differences from both Comfort (12.55) and Mild (12.75 mg/dL) (p<0.05). The increase in BUN concentrations with the increase of THI remained uncertain whether it was attributed to skeletal muscle breakdown or excessive ammonia production due to heat stress [ 13 , 35 ]. Otherwise, it may be due to an imbalance in protein metabolism due to a lack of energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BUN of Moderate (13.71) and Severe (14.39) showed differences from both Comfort (12.55) and Mild (12.75 mg/dL) (p<0.05). The increase in BUN concentrations with the increase of THI remained uncertain whether it was attributed to skeletal muscle breakdown or excessive ammonia production due to heat stress [ 13 , 35 ]. Otherwise, it may be due to an imbalance in protein metabolism due to a lack of energy.…”
Section: Resultsmentioning
confidence: 99%
“…Cortisol concentrations of Hanwoo calves in climatic controlled chambers were also higher at THI of 84 (15.9) and 88 (17.1) than that at 70 (4.8 ng/mL) [ 11 ]. Another research result [ 35 ] of Hanwoo steers in outside environments was that increased blood cortisol levels were observed after exposure to THI 80 to 87 (9.87) compared to THI 64 to 71 (1.91) and THI 72 to 79 (5.13 ng/mL). In addition, NIAS [ 18 ] reported that levels of blood cortisol in fattening stage of Hanwoo stress were 1 to 4 ng/mL in Mild, 5 to 6 ng/mL in Moderate and more than 6 ng/mL in Severe.…”
Section: Resultsmentioning
confidence: 99%
“…The higher RR and RT averages evaluated in the TS system at similar times represent a specific adaptation of the systems to metabolic needs or to the environment during these periods. In this way, the lack of varied management strategies based on the time of day and the rearing system can be studied in order to improve animal welfare and quality, leading to more effective practices in animal production [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heat stress (HS) increases WI in dairy cows [1,28] and Korean native beef steers [29] to compensate for sweat-induced water loss. Water losses through respiratory tract activity and thermoregulation mechanisms inherently result in an increased WI, which subsequently may lead to a decrease in DMI.…”
Section: Feed and Water Intake And Milk Yieldmentioning
confidence: 99%